Current State and Perspectives of Legal Support for Digital Transformation of the State Audit Office of Ukraine - L. V. Borets; V. O. Ruda (Bulletin of Kharkiv National University of Internal Affairs)
Improving the efficiency of the State Audit Office of Ukraine in exercising public financial control is largely determined by the success of the digital transformation of such activities. The legal support of such a process is important. The authors of the article outline the current state and perspectives of legal regulation of digital transformation of the State Audit Service of Ukraine for public financial control, identifies problems of legal regulation of digitalization of this service and ways to solve these problems. In particular, it is noted that one of the important issues is the legal regulation of the automated integrated information database on the status and results of state control over the management and use of state and local resources of the State Audit Service and other state control agencies, as well as databases and registers, the operation of which is financed from the state budget. Given the interdepartmental nature and the fact that the maintenance of some state registers is determined at the level of laws, the need to adopt a relevant law is not excluded. At the same time, appropriate amendments should be made to the Law of Ukraine "On Basic Principles of Public Financial Control in Ukraine", Regulations on the State Audit Office, Procedures for Inspection and Public Financial Audits, Inspection and Monitoring of Public Procurement, which should be supplemented by state financial control entities, in the order of information interaction or by direct access to them. In addition, it is impossible to solve the issue of digital transformation of the State Audit Office without raising the level of knowledge and appropriate training of its employees.